Mechanisms involved in regulation of Systemic Blood Pressure - Peysh A Patel; Noman Ali (Archives of Clinical Hypertension - Peertechz Publications, 2017)
Regulation of the circulatory system to maintain a constant arterial pressure is critical in ensuring adequate perfusion to meet metabolic requirements of tissues. Blood pressure (BP) can be considered in the context of Ohm's law, whereby BP (analogous to voltage) is directly proportional to the product of cardiac output (current) and total vascular resistance (TPR). Acute regulatory mechanisms are coordinated in the cardiovascular control centres in the brainstem, which are themselves infl uenced by impulses from other neural centres in addition to sensors both intrinsic and extrinsic to the circulation. However, certain organs such as the heart, kidneys and brain have the ability to coordinate blood flow locally, i.e. autoregulate. This enables alterations in regional perfusion without perturbations of BP. This mini-review provides an exploratory discussion of neural and humoral mechanisms that underpin regulation of systemic BP.